The influential impacts of international dynamic spillovers in forming investor preferences: a quantile-VAR and GDCC-GARCH perspective - Koursaros, Demetris; Dimitriadis, Konstantinos; Savva, Christos S. (My University, 2024)
This study investigates whether representative sectoral stock indices, gold, oil, Bitcoin, and wheat canmitigate risk and improve portfolio performance during normal times versus crises. The cutting-edgeQuantile Vector Autoregressive model and the Generalized Dynamic Conditional Correlations(Generalized-DCC) framework are adopted covering from 9 January 2017 until 30 August 2022.Econometric findings by the Q-VAR reveal that oil presents the strongest connection with commod-ities and stock indices and that Bitcoin and wheat despite their significant linkages with financialmarkets fail to act as safe havens. Moreover, GDCC-GARCH indicates that the returns of sectoralindices are weakly related but display powerful volatility co-movements. Gold serves efficiently asa hedger and oil follows and both act as better shelters during crises. Nevertheless, Bitcoin partlyabides by conventional markets in stressed periods. Notably, wheat reliably works as a hedger overallbut does not become a safe haven during crises.
Keywords: stocks; crises